УЛС ТӨРИЙН ДЭГЛЭМИЙН ШИЛЖИЛТ БА МОНГОЛЫН УЛС ТӨРИЙН ЭЛИТ - Ч.ӨЛЗИЙСАЙХАН; Ц.Өлзийжаргал (Politology, 2023)
There are different pictures of governing elites’ reputation due to political regime. Political dictatorship is an authority illness (authority syndrome) that occurs where normal public trust and support for authority is loosened. This type of political regime evolution can be abolished when public support is gained for the state where public living is increased in accordance to proper economic policy.